A rare case of intraoral trichilemmal cyst - Abrahao, Aline Corrêa; Daltoé, Felipe Perozzo; Santos, Valdirene Alves dos; Norberto Nobuo Sugaya; Pinto Jr, Décio dos Santos (Journal of Oral Diagnosis, 2016)
Trichilemmal cysts, also known as pilar cysts, are slow-growing lesions commonly found on the scalp of elderly women. They arise from outer root sheath epithelium and have a distinctive pattern of keratinization calledtrichilemmal keratinization. Here, we describe a rare case of a trichilemmal cyst on the lower lip mucosa of a 29-year-old man. The infrequency of intraoral hairs unquestionably results in the shortage of eported cases of trichilemmal cysts into the oral cavity.